2016
DOI: 10.18488/journal.31/2016.3.1/31.1.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Framework of Brand Image for Tourism Industry: Tourism Management and Advertisement as Moderators

Abstract: The conceptual framework of brand image for the tourism industry is a combination of antecedents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…In a travel setting, Latif et al (2015) find that brand image distinguishes the brand messages of competitive brands in a continuously changing market. Similarly, Quintal et al (2014) indicate that brand image includes ideas and assessments regarding positive characteristics of a tourist place.…”
Section: Brand Imagementioning
confidence: 99%
“…In a travel setting, Latif et al (2015) find that brand image distinguishes the brand messages of competitive brands in a continuously changing market. Similarly, Quintal et al (2014) indicate that brand image includes ideas and assessments regarding positive characteristics of a tourist place.…”
Section: Brand Imagementioning
confidence: 99%
“…Researchers 52 have thus focused on the consumer-centric approach of brand equity. The most cited work of Aaker 53 has defined CBBE as "a set of assets (and liabilities) linked to a brand's name and symbol that add to (or subtract from) the value provided by a product or service to a firm and/or that firm's customers."…”
Section: Customer-based Brand Equity (Cbbe)mentioning
confidence: 99%
“…The firms can thus understand their consumers’ expectations and delight them 50, 51 . Researchers 52 have thus focused on the consumer-centric approach of brand equity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the brand image also allied with the reputation and credibility (Wijaya, 2013). Latif et al (2015) indicated that brand image contribute important role in developing brand equity. By comparing the traditional and modern food truck, the modern food truck image is found more visible and recognizable (Loomis, 2013).…”
Section: Brand Imagementioning
confidence: 93%